Alkaloids from millipedes: a re-evaluation of defensive exudates from Polyzonium germanicum - Kunert, Olaf; Pferschy-Wenzig, Eva Maria; Orthaber, Andreas; Raspotnig, Günther; Bodner, Michaela (Frontiers in Ecology and Evolution, 2023)
Millipedes are known to produce various sets of chemical compounds in exocrine defensive glands to protect themselves against predators and microorganisms. Here, we reanalyzed the gland secretion of Polyzonium germanicum, a millipede of the order Polyzoniida, by using a combination of analytical techniques such as GC-MS, LC-HRMS and high field 1D and 2D NMR spectroscopy. Previously only one compound (polyzonimine, 1) had been described, but our approach allowed us to add six compounds to the defensive chemistry of this species. Besides polyzonimine (1), we found nitropolyzonamine (2) and five new compounds: 3 (2,3-dimethyl-7'-nitro-2',3',5',6',7',7a'-hexahydrospiro[cyclopent-2-ene-1,1'-pyrrolizine]), 4 (2,3-dimethyl-7'-nitro-2',3',5',6',7',7a'-hexahydrospiro[cyclopentane-1,1'-pyrrolizin]-2-ene), 5 ((1Z)-8,9-dimethyl-1-(nitromethylidene)-2-azaspiro[4.4]non-8-en-7-one), and not fully identified compounds A, B. For compounds 3 - 5 we were able to determine the molecular constitution, for two of them (4, 5) we were able to give relative configurations. Overall, the combination of advanced analytical techniques applied herein allowed detailed insights into the defensive chemistry of P. germanicum with a low number of individuals needed for analysis and without prior compound isolation.